Phosphoric acid functional UV-cured proton conducting polymer membranes for fuel cells - KAYAMAN APOHAN, NİLHAN (SPRINGER HEIDELBERG, 2015)
This paper reports the preparation and characterization of 10-methacryloyloxydecyl-dihydrogenphosphate (MDP)-based UV-curable proton-conducting polymer membranes (UVcPMs). Poly(ethylene glycol diacrylate) (PEGDA), as cross-linking agent, and N-vinyl-2-pyrrolidone (NVP), as reactive diluent, were used to arrange the mechanical and physical properties of the resulting membrane. The membrane formulation polymerized under UV irradiation and membranes were characterized by using Fourier transform infrared (FT-IR), thermal gravimetric analysis (TGA) and electrochemical impedans spectroscopy (EIS). The water uptakes, the volume swelling ratio and ion exchange capacity (IEC) measurement of the membranes were performed. The IEC values increase with an increase in MDP monomer content. Proton conductivities were measured as a function of the weight fraction of MDP content of the membrane. The conductivities are of the order of 10(-4)-10(-3) Scm(-1). The morphology of the membranes was also investigated by Atomic Force Microscopy (AFM). MDP-based UV-cured polymers are first reported as polyelectrolyte membranes.
Keywords: Photopolymerization; Conducting polymers; Membranes; Batteries and fuel cells; INTERMEDIATE TEMPERATURE; ELECTROLYTE MEMBRANES; EXCHANGE MEMBRANES; PROTOGENIC GROUP; POLYSULFONE IONOMERS; SULFONIC-ACID; NANOCOMPOSITE; PERFORMANCE; BLENDS; POLYBENZIMIDAZOLE